2016
DOI: 10.1177/1045389x16641199
|View full text |Cite
|
Sign up to set email alerts
|

Achieving biocompatible stiffness in NiTi through additive manufacturing

Abstract: This article seeks to reduce the stiffness of NiTi parts from a nonporous state to that of human bone by introducing porosity. Compact bone stiffness is between 12 and 20 GPa while the currently used bone implant materials are several times stiffer. While very stiff implants and/or fixation hardware can temporarily immobilize healing bone, it also causes stress shielding of the surrounding bone and commonly results in stress concentrations at the implant or immobilization hardware’s fixation site(s). Together … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(25 citation statements)
references
References 63 publications
1
24
0
Order By: Relevance
“…Porous NiTi scaffolds are often fabricated with the purpose of altering mechanical properties such as stiffness (i.e., modulus of elasticity) in order to match to the bone stiffness [6,98,103]. However, one should note that introducing porosity also affect other mechanical properties.…”
Section: Mechanical Properties Of Engineered Porous Nitimentioning
confidence: 99%
“…Porous NiTi scaffolds are often fabricated with the purpose of altering mechanical properties such as stiffness (i.e., modulus of elasticity) in order to match to the bone stiffness [6,98,103]. However, one should note that introducing porosity also affect other mechanical properties.…”
Section: Mechanical Properties Of Engineered Porous Nitimentioning
confidence: 99%
“…There is a growing interest in additive manufacturing (AM) of TiNi shape memory alloys (SMAs), as they provide an interesting combination of functional performance due to the shape memory effect (SME), as well as unique mechanical and physical properties (e.g. low elastic modulus, biocompatibility [1,2], mechanical strength, and excellent corrosion and wear resistance [3,4]). They have been employed in biomedical implants and devices [5], aerospace components [6], and functional devices [7].…”
Section: Introductionmentioning
confidence: 99%
“…Vacuum casting is essential to avoid increasing the impurity levels (O, C, and N), which could generate TiC, TiO 2 , and Ti 4 Ni 2 O X secondary phase particles, which degrade the functional and mechanical properties of TiNi SMAs [4,8]. PM will also result in impurity pick-up, and is limited in its geometrical complexity [2]. Machining of TiNi encounters significant tool wear owing to the intrinsic mechanical behaviour of SMAs, making it essential to use special machining processes (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…An Abaqus user-defined material subroutine (UMAT) developed based on the micro-plane theory [37][38][39] was used for capturing the mechanical behavior of the NiTi bone fixation plates. The UMAT is capable of simulating both superelastic and shape memory effects of shape memory alloys under multiaxial loading conditions [15] and requires the thermomechanical properties of the standard coupons (e.g., Young's modulus for austenite and martensite, transformation temperatures, critical stresses, etc.) as the input.…”
Section: Modelingmentioning
confidence: 99%
“…Although NiTi has a relatively lower level of stiffness, it still provides a higher level of stiffness in comparison to the bone tissue. We have shown that by introducing an engineered level and type of porosity to a bone fixation plate, one is able to further reduce the stiffness of NiTi bone fixation plates and reach the level of bone tissue [15,16]. We have also shown that the additive manufacturing method, in the form of selective laser melting (SLM), can be used for the fabrication of porous NiTi bone fixation plates [17,18].…”
Section: Introductionmentioning
confidence: 99%